2017
DOI: 10.3390/coatings7080129
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Triboemission Imaging and Charge Measurements to Study DLC Coating Failure

Abstract: We present a study on the simultaneous evolution of the electron emission and surface charge accumulation that occurs during scratching tests in order to monitor coating failure. Steel discs coated with a diamond-like-carbon (DLC) film were scratched in both vacuum (~10 −5 Torr) and atmospheric conditions, with electron emission and surface charge being measured by a system of microchannel plates and an electrometer, respectively. The results highlight a positive correlation between emission intensity values, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…A diamond-like coating (DLC) was obtained by sputtering a graphite target in a glow discharge plasma, resulting in an amorphous coating structure consisting of carbon atoms with both diamondand graphite-like bonds [44,45]. This coating is traditionally characterized by a low friction coefficient and has noticeably higher microhardness values in comparison to tool ceramics.…”
Section: Deposition Of Vacuum-plasma Coatings On Ceramics and Coatingmentioning
confidence: 99%
“…A diamond-like coating (DLC) was obtained by sputtering a graphite target in a glow discharge plasma, resulting in an amorphous coating structure consisting of carbon atoms with both diamondand graphite-like bonds [44,45]. This coating is traditionally characterized by a low friction coefficient and has noticeably higher microhardness values in comparison to tool ceramics.…”
Section: Deposition Of Vacuum-plasma Coatings On Ceramics and Coatingmentioning
confidence: 99%
“…Despite being one of the most known and long studied physical phenomena, triboelectrification is still poorly understood 5,6 and the mechanism behind it is still under debate especially for insulatorinsulator contact. Several theories have suggested that the electrification is due to the transfer of electrons [7][8][9][10][11][12][13] , ions [14][15][16][17] or microscopic fragments of material [18][19][20][21] that act as charge carriers, however, no consensus has been yet achieved. This lack of fundamental understanding of triboelectrification hinders the development and the improvement of effective TENGs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tribological properties of DLC films depend on not only the intrinsic parameters, but also many extrinsic factors, such as sliding velocity, normal load, environment atmosphere, and properties of friction interfaces [12][13][14][15]. In particular, the effect of sliding velocity on the friction characteristics of DLC films has been extensively studied, giving rise to a large amount of diverging findings [15][16][17]. For instance, it is noted that the friction coefficient of the DLC films increased from 0.07 to 0.22 with increasing of sliding velocity in air, and the reason is due to the entrapment of more debris particles at the sliding interface [18].…”
Section: Introductionmentioning
confidence: 99%